THE USE OF BIOCHAR FOR REMOVAL OF EMERGING CONTAMINANTS IN CONTAMINATED WATER - Medran Rangel, Adrize; Medran Rangel, Eduarda; Wickboldt Stark, Fernanda; de Borba Pereira, Patr´ícia; Machado Machado, Fernando (Journal of Interdisciplinary Debates, 2023)
Biochar is a product that has been gaining prominence in the scientific community, and its applicability in the treatment of contaminated environments has been studied all over the world. Its characteristics such as yield and properties vary greatly with the type of raw material, production technology and operational parameters applied. Emerging contaminants are a global concern and need attention, so the use of bugs to remove these contaminants is a viable alternative. The objective of this research is to analyze how the authors are using biochar to treat water and effluents contaminated with emerging contaminants. The articles were searched in reputable databases, such as Science Direct and SciElo, after careful analysis, 15 articles on the subject of study were evaluated. Researchers and decision makers bring important results in their research on the most efficient ways to choose raw materials for biochar production, implementing sustainable production technologies and presenting satisfactory results in the removal of emerging contaminants. Through the data analyzed, it was possible to conclude that biochar is a promising, low-cost, highly replicable material that often uses solid waste from other production processes as raw material and efficiently removes contaminants emerging from aqueous media.